Illuminatable Laminated Interlayers and Glass
Patent Information
- Application Number
- JP2022500837
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-10
- Filing Date
- 2020-07-09
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2040-07-09
AI Technical Summary
【0009】 可塑剤をほとんど又は全く含まないポリビニルブチラール(PVB)ポリマー中間層膜(102)を使用する1つの利点は、特に平滑な表面を有するフィルム、これにより平滑な面に対するより良好で均一な印刷画像を生成可能なことである。また、膜102に使用されるポリビニルブチラール材料は、当然のことながら、ガラス産業で使用される標準のPVB中間層と非常に適合性がある。さらに、可塑剤を含まない、これにより、剛性のあるPVB膜102は、フレキソ印刷などの新しい、より経済的なロールツーロールプロセスを使用して印刷できる。これは、ガラス又は軟質PVB膜では不可能である。
Smart Images

Figure 0007645225000001 
Figure 0007645225000002
Abstract
Description
[Technical field]
[0001] Transparent laminate interlayers and laminate structures are described that allow for the application of optically enhanced functional layers, structures or patterns, particularly for transparent lighting and display applications. [Background technology]
[0002] Transparent surfaces, especially glass facades of buildings or automotive glass, are increasingly being subject to functionalization. The main areas of interest are the control of transmitted daylight, lighting and the display of information. In the automotive market, the lighting of transparent glass surfaces is of particular importance.
[0003] DE 10204359 A1 describes a device for illuminating a sunroof for a motor vehicle. However, the structure of the device described there is rather complicated and leads to an increase in the thickness of the sunroof part, which inevitably leads to a decrease in the driver's head space and an increase in the vehicle weight.
[0004] DE 10 2012 109 900 B4 describes illuminable glass for automobile passenger sunroofs, which comprises a light-guiding layer made of embedded light-scattering particles or a physically modified surface. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] DE 10204359 A1 [Patent Document 2] German Patent No. 102012109900 Summary of the Invention [Problem to be solved by the invention]
[0006] However, there remains a need for improved illuminable glass.
[0007] Thus, one object of the present invention is a laminated glass with improved manufacturing costs, raw material costs, and / or improved environmental footprint. Another object of the present invention is to provide a laminated glass with improved characteristics, such as improved thermal stability, improved optical properties such as improved haze, clarity and / or transmission, and / or improved design features.
[0008] Therefore, in a first aspect, the present invention provides a laminated glass comprising two glass sheets (101, 105) and at least one polymer interlayer film (102) between the two glass sheets, characterized in that a functional layer (103) containing light-scattering particles is applied to at least one surface of the polymer interlayer film (102), the polymer interlayer film (102) comprises polyvinyl butyral and optionally a plasticizer W, and the content of plasticizer W in the polymer interlayer film (102) before lamination is 5% or less. [Means for solving the problem]
[0009] One advantage of using a polyvinyl butyral (PVB) polymer interlayer film (102) that contains little or no plasticizers is that it produces a film with a particularly smooth surface, which allows for better and more uniform printed images on smooth surfaces. Also, the polyvinyl butyral material used in the film 102 is naturally very compatible with standard PVB interlayers used in the glass industry. Furthermore, being free of plasticizers, this allows the rigid PVB film 102 to be printed using newer, more economical roll-to-roll processes such as flexography, which is not possible with glass or flexible PVB films. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 shows one embodiment of the laminated glass structure of the present invention according to Example 1. [Diagram 2] FIG. 2 shows a further embodiment of the laminated glass structure of the invention according to Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Preferably, the polymer interlayer film (102) also comprises a (meth)acrylate, a poly(vinyl) acetal, an ionomer such as ethylene methacrylic acid copolymer, nitrocellulose, polystyrene, a thermoplastic polyurethane, a polycarbonate, a polyvinyl chloride, a polyolefin such as polyethylene or polypropylene, polyethylene terephthalate, ethylene vinyl acetate, or a mixture thereof.
[0012] The light scattering particles are typically applied to at least one surface of the polymer interlayer film (102) by a coating or printing method, in which case the light scattering particles can be applied via techniques commonly known in the printing industry, such as offset printing, rotary gravure printing, flexographic printing, screen printing, and inkjet printing.
[0013] The thickness of the functional layer (103) before lamination is preferably 0.1 μm to 100 μm, and more preferably 1.0 μm to 20 μm.
[0014] The functional layer (103) preferably comprises light scattering particles and at least one matrix material. Suitable matrix materials include polymers that can disperse the light scattering particles uniformly without decomposition. Preferably, the matrix material comprises homo- or copolymers of (meth)acrylates, methyl methacrylate, poly(vinyl)acetal, nitrocellulose, polystyrene, polyvinyl alcohol, polyurethane, polycarbonate and polyvinyl chloride. Most preferably, the matrix material is polyvinyl butyral.
[0015] Further components may be present in the functional layer (103), examples of which include co-resins, solvents, UV absorbers, UV stabilizers, crosslinkers, curing agents, accelerators, photoinitiators, surfactants, stabilizers, fillers, thixotropic modifiers and plasticizers.
[0016] Any light scattering material known in the art can be used. Preferably, the light scattering particles are selected from the group consisting of TiO2, ZnO, Al2O3, ZrO2, PbSO4, BaSO4, CaCO3, glass, polymers, and mixtures thereof. The light scattering particles can be used as solid or hollow beads or fibers.
[0017] Preferably, the light scattering particles are present in the functional layer (103) in an amount of 0.1 to 10% by weight, more preferably 0.5 to 5% by weight, and most preferably 1 to 2.5% by weight.
[0018] Also preferably, the light scattering particles have a median particle size D50 by volume determined by laser diffraction according to DIN 13320 of 0.001 μm or more, more preferably 0.01 μm or more, 0.05 μm or more, or 0.1 μm or more. Also preferably, the median particle size D50 is 10.0 μm or less, more preferably 5.0 μm or less, most preferably 1.0 μm or less. Preferably, the median particle size by volume determined by laser diffraction according to DIN 13320 is 0.01 μm or more and 1.0 μm or less.
[0019] Preferably, the light scattering particles are present in the functional layer (103) in the form of a concentration gradient, i.e. the concentration of functional particles in the functional layer (103) varies depending on the distance to the light source. More preferably, the concentration of light scattering particles in the functional layer (102) increases as the distance to the nearest light source increases.
[0020] In one embodiment, the laminated glass of the present invention is used as an automobile glass. Preferably, the second glass sheet (105) faces the outside of the vehicle. Also preferably, the laminated glass of the present invention is used in a sunroof. In that case, the second glass sheet (105) may be tinted to reduce the solar energy transmitted through the laminate to the vehicle, and thus may show increased absorption. Such highly light-absorbing sheets are not particularly suitable as light guides.
[0021] Preferably, the functional layer (103) completely covers at least one surface of the polymer interlayer film (102).
[0022] Also preferably, the functional layer (103) covers only a part of the polymer interlayer film (102). Thus, the functional film (103) can be applied in the form of a pattern, achieving illumination in the form of a specific pattern, which is not possible if the light scattering particles are distributed uniformly in the laminate. Thus, preferably, the functional film (103) covers no more than 90%, no more than 80%, no more than 75%, most preferably less than 50% of at least one surface of the polymer interlayer film (102). This embodiment is particularly useful for use in useful and / or decorative glass for aircraft, trains or ships, and in construction areas, especially for show windows, elevators or facade glass.
[0023] The thickness of the functional layer (103), as measured by an IR microscope, is preferably 0.1 to 50 μm, more preferably 1 to 30 μm, and most preferably 2 to 20 μm.
[0024] In the present invention, optically transparent means completely optically transparent as well as translucent. Optically transparent therefore means that at least 40% of the initial light passes through the device comprising layer (103), even more preferably 50-100%, and even more preferably 80-100%. The transparency (light transmittance) is determined as the light transmittance TL (380-780 nm) according to DIN EN 410 on a test laminate using two standard panes of clear glass.
[0025] For the avoidance of doubt, light transmittance is measured in an area of the test laminate containing the functional layer (103) and compared to an area not containing the functional layer (in the same laminate or, in the case where the functional layer (103) completely covers the surface of the polymer interlayer film (102), in a test laminate prepared without the functional film (103) using the same type of film).
[0026] To avoid haze in the polymer interlayer film (102) and (102A), the amount of chloride ions and / or nitrate ions and / or sulfate ions in any of the different layers may be reduced. Thus, the chloride content may be less than 150 ppm, preferably less than 100 ppm, in particular less than 50 ppm. Most preferably, the chloride content is less than 10 ppm. The nitrate content may be less than 150 ppm, preferably less than 100 ppm, in particular less than 50 ppm. Most preferably, the nitrate content is less than 10 ppm. Again, optionally, the sulfate content may be less than 150 ppm, preferably less than 100 ppm, in particular less than 50 ppm, in particular less than 10 ppm.
[0027] Also, preferably, the polymer interlayer film (102) contains polyvinyl butyral and a plasticizer W, and the content of the plasticizer W in the polymer interlayer film (102) before lamination is 20% or less, more preferably less than 15%, more preferably less than 10% or less than 5%, more preferably less than 0.5%, or more preferably, the polymer interlayer film is free of added plasticizer.
[0028] The term "pre-lamination" is intended to mean the state before the film is in contact with any of the other components of the laminated glass of the present invention.
[0029] In the case of polyvinyl butyral, the film is generally produced by extrusion using a cast film line or in the form of a blown film. Here, the surface roughness may be produced by controlled melt fracture or further using the cast film method by the use of a structured chill roll and / or a structured back roll. Preferably, at least one surface of the polymer interlayer film (102) has a roughness Rz of 10 μm or less, measured according to EN ISO 4287, before lamination. The polymer interlayer film (102) used according to the present invention preferably has a single-sided structure with a roughness Rz of less than 25 μm, preferably between 0.1 and 10 μm, more preferably between 1 and 5 μm. This smooth surface allows light scattering particles to be applied in a very uniform manner to the surface of the polymer interlayer film (102) resulting in a high-quality optical pattern of the illuminated glass.
[0030] The other surface of the polymer interlayer film may have a roughness as described above.
[0031] However, conventional lamination interlayers formed from polyvinyl butyral typically have a rougher surface to ensure proper degassing during the lamination process. The roughness of such films typically ranges from 20 to 80 μm in Rz value. Thus, the other surface of the polymer interlayer film may have a roughness of 0.1 to 50 μm, preferably 1 to 20 μm, more preferably 5 to 10 μm.
[0032] Preferably, the polymer interlayer film (102) has a thickness of 10 μm to 250 μm, more preferably 20 to 160 μm, most preferably 30 to 120 μm, also preferably 40 to 100 μm, specifically 50 to 80 μm, before lamination. This thickness range does not include any additional coatings on the film. It is particularly preferred that these thin polymer interlayer films have low or no plasticizer content or no plasticizer, as described above, to avoid sticking problems and to exhibit the necessary stiffness for printing and processing such thin films.
[0033] In another embodiment of the invention, the laminated glass comprises, in that order, a first glass sheet (101), a further polymer interlayer film (102A), a functional layer (103), a polymer interlayer film (102), and a second glass sheet (105).
[0034] Specifically, the further polymer interlayer film (102A) comprises polyvinyl butyral. Preferably, at least one surface of the further polymer interlayer film (102A) has a roughness Rz of 20 to 80 μm, more preferably 25 to 70 μm, and most preferably 30 to 60 μm, measured according to EN ISO 4287 before lamination. Preferably, the other surface has a roughness Rz of 20 to 80 μm, more preferably 25 to 70 μm, and most preferably 30 to 60 μm, measured according to EN ISO 4287 before lamination.
[0035] Further, the polymer interlayer film (102A) may be any plasticized PVB film known in the art, i.e., containing at least 22% by weight of plasticizer prior to lamination, such as 22.0-45.0% by weight, preferably 25.0-32.0% by weight, especially 26.0-30.0% by weight, of plasticizer alone or in mixtures of plasticizers.
[0036] Suitable plasticizers include one or more compounds selected from the following group: esters of polyhydric aliphatic or aromatic acids, for example dialkyl adipates, such as dihexyl adipate, dioctyl adipate, hexylcyclohexyl adipate, mixtures of heptyl adipate and nonyl adipate, diisononyl adipate, heptylnonyl adipate, and esters of adipic acid with cycloaliphatic ester alcohols or with ether compound-containing ester alcohols; dialkyl sebacates, such as dibutyl sebacate, and esters of sebacic acid with cycloaliphatic ester alcohols or with ether compound-containing ester alcohols; esters of phthalic acid, such as butyl benzyl phthalate or bis-2-butoxyethyl phthalate. - esters or ethers of polyhydric aliphatic or aromatic alcohols or oligoether glycols having one or more unbranched or branched aliphatic or aromatic substituents, such as esters of glycerol, diglycol, triglycol or tetraglycol with linear or branched aliphatic or alicyclic carboxylic acids; Phosphates with aliphatic or aromatic ester alcohols, such as tris(2-ethylhexyl) phosphate (TOF), triethyl phosphate, diphenyl-2-ethylhexyl phosphate, and / or tricresyl phosphate. - Esters of citric acid, succinic acid and / or fumaric acid.
[0037] Particularly preferred are 1,2-cyclohexanedicarboxylic acid diisononyl ester (DINCH) or triethylene glycol-bis-2-ethylhexanoate (3GO or 3G8).
[0038] Additionally, the polymer interlayer films (102 and (102A) may contain additional additives, such as It may contain residual amounts of water, UV absorbers, antioxidants, adhesion modifiers, optical brighteners or fluorescent additives, stabilizers, colorants, processing aids, inorganic or organic nanoparticles, pyrogenic silicic acid and / or surface active substances.
[0039] Alternatively, the polymer interlayer film (102) and / or the further polymer interlayer film contain less than 0.15% by weight, and more preferably no UV absorbers, to avoid color shifts in visible light.
[0040] Before lamination, the thickness of the additional polymer intermediate layer film (102A) is preferably 250 to 2500 μm, more preferably 300 to 1600 μm, more preferably 380 to 1200 μm, and most preferably 600 to 900 μm.
[0041] To ensure sufficient degassing during the lamination process, it is particularly preferred to use a polymer interlayer film (102), (102A) having at least one roughened surface, positioned so that the roughened surface is in contact with the glass plates (101, 105).
[0042] Depending on where the final glass will be used, for example in the case of an automobile sunroof, the second glass pane (105) facing the sun may often be tinted to reduce the amount of solar energy transmitted through the laminate into the vehicle. Thus, an optical isolation layer (104) may be used between the optionally tinted glass pane (105) and the light source to reduce the amount of light entering the glass pane (105) that would be absorbed and lost for lighting purposes.
[0043] Therefore, another embodiment of the invention relates to a laminated glass comprising, in that order, a first glass sheet (101), a further polymer interlayer film (102A), a functional layer (103), a polymer interlayer film (102), an optical isolation layer (104), and a second glass sheet (105).
[0044] The optical isolation layer (104) may consist of any medium capable of preventing a major amount of light from entering the glass plate (105). A typical laminate interlayer is not very suitable as the optical isolation layer (104) because of its refractive index close to that of the transparent glass plates (101, 105). Therefore, the refractive index of the optical isolation layer (104) must be significantly lower. The lower the refractive index of the optical isolation layer (104), the more efficient the light guide and illumination. Suitable materials exhibit sufficient adhesion, cohesion, and mechanical strength to allow a strong bond between the adjacent layers (102) and (105). Suitable materials include polymers or inorganic materials or composites thereof. Furthermore, the low refractive index layer may consist of a nanoscale porous material that allows the incorporation of a low refractive index fluid in its pores.
[0045] In another configuration, the low index layer can be chosen to be a simple gap that is filled with air or another gas, in a similar manner to that of a typical insulating glass unit. In another embodiment, the gap can be chosen not to be filled, and thus a vacuum can be provided in a similar manner to vacuum insulating glass. In the latter case, the gap must be held in place by small spacers in the form of printed dots to prevent it from collapsing. The spacers are preferably made of a non-transparent, preferably white, material.
[0046] An essential part of the final application is the light source (106), which provides light that is coupled to the light guide layers (101) and (102) via the optical connector (107). The optical connector (107), which is a transparent, optically transparent material with low light absorption, may form a permanent bond between the light source (106) and the light guide layers (101) and (102), for example by physical and / or chemical curing, an optically transparent adhesive, or by a positive-fit or force-fit connection. In the latter case, the maintainability can be improved, for example changing the light source (106). Suitable materials for a positive-fit or force-fit are optically transparent polymers, especially elastomers. The light source (106) can be any conventional light source, preferably it is an LED light source.
[0047] A second aspect of the present invention is a method for producing a laminated glass as described above, comprising a step in which a functional film (103) is applied to the polymer interlayer film (102) by a printing or coating method.
[0048] The glass sheets (101, 105) and the various interlayer films can be laminated by any known lamination technique known in the art. Preferred aspects of the present invention include the following. [1] A laminated glass comprising two glass sheets (101, 105) and at least one polymer interlayer film (102) between the two glass sheets, characterized in that a functional layer (103) containing light-scattering particles is applied to at least one surface of the polymer interlayer film (102), the polymer interlayer film (102) contains polyvinyl butyral and optionally a plasticizer W, and the content of the plasticizer W in the polymer interlayer film (102) before lamination is 5% or less. [2] The laminated glass according to [1], wherein the polymer interlayer film (102) comprises a (meth)acrylate, a poly(vinyl)acetal, an ionomer such as ethylene methacrylic acid copolymer, nitrocellulose, polystyrene, a thermoplastic polyurethane, a polycarbonate, a polyvinyl chloride, a polyolefin such as polyethylene or polypropylene, a polyethylene terephthalate, an ethylene vinyl acetate, or a mixture thereof. [3] The laminated glass according to [2], wherein the polymer interlayer film (102) contains poly(vinyl) butyral. [4] The light scattering particles are TiO 2 , ZnO, Al 2 O 3 , ZrO 2 , PbSO 4 , BaSO 4 , CaCO 3 The laminated glass according to any one of [1] to [3], wherein the laminated glass is selected from the group consisting of glass, a polymer, and a mixture thereof. [5] The laminated glass according to any one of [1] to [4], wherein the light-scattering particles have a median particle size D50 by volume determined by a laser diffraction method in accordance with DIN 13320 of 0.01 μm or more and 1.0 μm or less. [6] The laminated glass according to any one of [1] to [5], wherein the functional layer (103) has a light transmittance TL (380 to 780 nm) measured in accordance with DIN EN 410 of 80% or more before lamination. [7] The laminated glass according to any one of [1] to [6], wherein the polymer interlayer film (102) contains polyvinyl butyral and does not contain a plasticizer. [8] The laminated glass according to any one of [1] to [7], wherein at least one surface of the polymer interlayer film (102) has a roughness Rz of 10 μm or less before lamination. [9] The laminated glass according to any one of [1] to [8], wherein the polymer intermediate layer (102) has a thickness of 10 μm or more and 250 μm or less before lamination.
[10] The laminated glass according to any one of [1] to [9], comprising, in this order, a first glass plate (101), a further polymer interlayer film (102A), a functional layer (103), a polymer interlayer film (102), and a second glass plate (105).
[11] The laminated glass according to any one of [1] to [9], comprising, in this order, a first glass plate (101), a polymer interlayer film (102), a functional layer (103), a further polymer interlayer film (102A), and a second glass plate (105).
[12] The laminated glass according to any one of [1] to
[11] , wherein the laminated glass has a light transmittance of 80% or more.
[13] The laminated glass according to any one of [1] to
[10] , comprising, in this order, a first glass plate (101), a further polymer interlayer film (102A), a functional layer (103), a polymer interlayer film (102), an optical separation layer (104), and a second glass plate (105).
[14] The laminated glass according to any one of [1] to
[13] , further comprising a light source (106) and an optical connector (107) in contact with the first glass plate (101).
[15] A method for producing a laminated glass according to any one of [1] to
[13] , comprising a step of applying the functional layer (103) to the polymer interlayer film (102) by a printing or coating method. EXAMPLES
[0049] Working Example To form the printing ink for the functional layer (103), 0.40 wt. % titanium dioxide (as light scattering particles) with a particle size D50 of 0.15 μm determined by laser diffraction according to DIN 13320, 27.0 wt. % poly(methyl methacrylate) (PMMA) (as matrix material), 36.3 wt. % 2-butoxyethanol acetate, and 36.3 wt. % cyclohexanone (as sacrificial solvents) were selected.
[0050] Example 1 A 50 μm thick polyvinyl butyral interlayer without added plasticizer was used. The substrate had a side A with a roughness Rz of 10 μm and a side B with a roughness Rz of 5 μm. The functional layer was applied to side B of the interlayer by screen printing with the printing ink described above. A screen with 120 threads / cm and a thread diameter of 34 μm was used. The screen was pretreated with a partially cured light emulsion to form the desired printing pattern of a 5 cm x 10 cm rectangle. The printed ink was allowed to dry for 30 minutes at room temperature. The printed substrate was then placed on a sheet of regular float glass with a thickness of 2 mm, with the unprinted side A in direct contact with the glass. On top of the printed side B of the substrate, a regular plasticized polyvinyl butyral interlayer (0.76 mm, Trosifol® UltraClear available from Kuraray Europe GmbH) was placed. On top of this second interlayer, a second sheet of regular float glass with a thickness of 2 mm was placed. All layers were A4 size and fixed in the above order by applying adhesive tape to the outer glass plates. The stack was then prelaminated in a vacuum bag by applying vacuum at room temperature for 15 minutes followed by another 15 minutes at 110° C. After prelamination, the prelaminate was autoclaved in an autoclave at 140° C. and 12 bar pressure for 90 minutes.
[0051] The low roughness of side B of the first polyvinyl butyral interlayer resulted in a more uniform illumination of the printed areas compared to laminates made with a standard printed laminate interlayer such as Trosifol® UltraClear from Kuraray Europe GmbH, which has a higher roughness. Furthermore, a high visible light transmission (TL) (380-780 nm) measured according to DIN EN 410 was achieved in the printed areas of the laminate.
[0052] TL[%] Print area 88.0 Unprinted area 89.5 △ 1.50
[0053] Example 2 A polyvinyl butyral interlayer with no added plasticizers and a thickness of 50 μm is used. The substrate has a side A with a roughness Rz of 10 μm and a side B with a roughness Rz of 5 μm. The functional layer is applied to side B of the substrate by screen printing using the printing ink described above. A screen with 120 threads / cm and a thread diameter of 34 μm is used. The screen has been previously treated with a light emulsion that is partially cured to form the desired printing pattern of a 5 cm x 10 cm rectangle. The printed ink is dried for 30 minutes at room temperature. The printed substrate is then placed on a plate of low-iron glass with a thickness of 2 mm, so that the non-printed side A is in direct contact with the glass. On top of the printing side B of the substrate, a regular plasticized polyvinyl butyral interlayer (thickness: 0.76 mm, Trosifol® UltraClear available from Kuraray Europe GmbH) is placed. On top of this thicker interlayer is placed a 2 mm thick tinted glass sheet with a visible light transmittance TL (380-780 nm) of 10% measured in accordance with DIN EN 410. The tinted glass sheet has a normal side A and a side B facing the interlayer and coated with a low refractive index coating with a refractive index of 1.25.
[0054] All layers were A4 size and fixed in the above order by applying adhesive tape to the outer glass plates. The stack was then prelaminated in a vacuum bag by applying vacuum at room temperature for 15 minutes followed by another 15 minutes at 110° C. After prelamination, the prelaminate was autoclaved in an autoclave at 140° C. and 12 bar pressure for 90 minutes.
[0055] Even within such a stack including a highly absorbing tinted glass sheet 105, the functional layer 103 can be fully illuminated because the low refractive index coating 104 optically isolates the tinted glass sheet 105 from the light guide layers 101, 102, 103 and 102A.
[0056] Example 3 A 1.05 m wide plasticizer-free polyvinyl butyral film with a thickness of 35 μm, a surface roughness of 1 μm on the top side and a surface roughness of 5 μm on the bottom side was used in double with a 40 μm thick OPP carrier film on the bottom side. The OPP carrier film was rolled without the application of heat to form a temporary unit with the thin PVB, and essentially held together by electrostatic forces to stabilize the web during the printing process and prevent contamination or ink transfer to the unprinted side of the PVB. The PVB side of the temporary bi-lam was printed on a flexographic press with a water-based ink essentially containing polyurethane binder, 1% titanium dioxide, ink additives, and water as suspension. An EPDM printing sleeve with a continuous dot pattern (dot diameter 1 mm, horizontal and vertical dot spacing 2 mm) was used as the printing master. The ink transfer amount was 3 g / m2. 2 An anilox roller of 100 mm was selected and the film was printed at a speed of 60 m / min and wound into a roll. The resulting thickness of the dried layer of the ink was in the range of 1 μm. A 50x50 cm glass / glass laminate with a light diffusing interlayer and a standard PVB interlayer was constructed in the following way: A 2.1 mm Planiclear® glass of the above dimensions was prepared by cleaning it in dust-free conditions, the OPP carrier film was carefully removed and the 35 μm printed PVB was placed on the first glass with the printed side facing up and the 5 μm rough bottom side in contact with the glass surface. TROSIFOL® NR200 was placed on top of the printed PVB and the assembly was completed with the second glass. Lamination was performed using the same overall process conditions from above with a standard rubber bag. The resulting laminate showed little visual haze on inspection (dots are practically invisible when inspecting the laminate under normal lighting). An LED bar is attached to one end of the stack, and when lit up, the corresponding bright colors combine to create the illusion of a lit dot pattern.
[0057] The above laminate was compared to an area of a laminate of the same construction, but in which the dot printed film was replaced with unprinted 35 μm film.
[0058] The visible light transmittance TL and haze were measured according to ISO 9050 and ASTM D 1003. The results show that, despite its good light diffusion properties, the light diffusing print of thin PVB only slightly reduces the TL and slightly increases the visible haze.
[0059] TL[%] Print area 88.0 Unprinted area 89.5 △ 1.50
Claims
1. A laminated glass comprising two glass sheets (101, 105) and at least one polymer interlayer film (102) between the two glass sheets, wherein a functional layer (103) containing light scattering particles is applied to at least one surface of the polymer interlayer film (102), the polymer interlayer film (102) contains polyvinyl butyral and optionally a plasticizer W, the content of the plasticizer W in the polymer interlayer film (102) before lamination is 5% or less, the surface of the polymer interlayer film (102) to which the functional layer (103) is applied has a roughness Rz of 10 μm or less before lamination, and the surface of the polymer interlayer film (102) to which the functional layer (103) is not applied has a roughness Rz of 0.1 to 50 μm before lamination.
2. The light scattering particles are TiO 2 , ZnO, Al 2 O 3 , ZrO 2 , PbSO 4 , BaSO 4 , CaCO 3 10. The laminated glass of claim 1, wherein the polymer is selected from the group consisting of glass, polymers, and mixtures thereof.
3. 3. The laminated glass according to claim 1, wherein the light-scattering particles have a median particle size D50 by volume, determined by laser diffraction according to DIN 13320, of 0.01 μm to 1.0 μm.
4. The laminated glass according to any one of claims 1 to 3, wherein the functional layer (103) has a light transmittance TL (380 to 780 nm) of 80% or more measured in accordance with DIN EN 410 before lamination.
5. The laminated glass of any one of claims 1 to 4, wherein the polymer interlayer film (102) is plasticizer-free.
6. The laminated glass according to any one of claims 1 to 5, wherein the polymer interlayer film (102) has a thickness of 10 μm or more and 250 μm or less before lamination.
7. 7. The laminated glass according to any one of claims 1 to 6, comprising, in that order, a first glass sheet (101), a further polymer interlayer film (102A), a functional layer (103), a polymer interlayer film (102), and a second glass sheet (105).
8. 7. The laminated glass according to any one of claims 1 to 6, comprising, in that order, a first glass sheet (101), a polymer interlayer film (102), a functional layer (103), a further polymer interlayer film (102A), and a second glass sheet (105).
9. The laminated glass according to any one of claims 1 to 8, wherein the laminated glass has a light transmittance of 80% or more.
10. 8. The laminated glass according to any one of claims 1 to 7, comprising, in that order, a first glass sheet (101), a further polymer interlayer film (102A), a functional layer (103), a polymer interlayer film (102), an optical isolation layer (104), and a second glass sheet (105).
11. The laminated glass of any one of claims 1 to 10, further comprising an optical connector (107) in contact with the light source (106) and the first glass sheet (101).
12. The method for producing laminated glass according to any one of claims 1 to 10, comprising a step in which the functional layer (103) is applied to the polymer interlayer film (102) by a printing or coating method.
Citation Information
Patent Citations
Vehicle glazing
DE102012109900A1
Roof part for vehicle has light field beneath roof part formed by illuminating it with light from illumination device and bearer surface illuminated by light from source forms light panel
DE10204359A1
Illumination glass panel for buildings, equipment or public transportation
JP2018518796A
Layered panel structure for sun-sky mimicking lighting system
JP2019503034A
Resin composition, film, and interlayer for laminated glass
WO2017200052A1